2021
DOI: 10.1002/jcu.23111
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of fetal precordial venous system by four‐dimensional ultrasound with spatiotemporal image correlation technology

Abstract: Despite the use of two-and three-dimensional color Doppler ultrasonography, the prenatal sonographic evaluation of precordial venous system remains difficult. Spatiotemporal image correlation (STIC) technology has been well described for the assessment of the fetal heart, but not of precordial venous system. As demonstrated in this report, it is feasible to use four-dimensional ultrasound with STIC rendered volume in glass-body mode and tomographic ultrasound imaging to image this system including the connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Although the pulsatile blood flow in the IPB and spiral artery jets are in opposite directions and their pulse rates are different, STIC algorithm can calculate an average flow rate across all the acquired blood‐flow images and rearrange the latter accordingly 10 . It is well known that glass‐body mode can be used to show the heart cycle‐related flow events and the spatial relationship of the vascular structures 4,5 . A recent study has showed that it is feasible to use B‐flow/STIC M‐mode ultrasonography to study uterine spiral artery blood flow during the cardiac cycle in a non‐human primate model 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pulsatile blood flow in the IPB and spiral artery jets are in opposite directions and their pulse rates are different, STIC algorithm can calculate an average flow rate across all the acquired blood‐flow images and rearrange the latter accordingly 10 . It is well known that glass‐body mode can be used to show the heart cycle‐related flow events and the spatial relationship of the vascular structures 4,5 . A recent study has showed that it is feasible to use B‐flow/STIC M‐mode ultrasonography to study uterine spiral artery blood flow during the cardiac cycle in a non‐human primate model 11 …”
Section: Discussionmentioning
confidence: 99%
“…The use of color Doppler with spatiotemporal image correlation (STIC) in glass-body mode can demonstrate the heart cycle-related flow events and assess the spatial relationship of blood vessels. 4,5 The objective of the present report is to describe a novel application of STIC technique to examine the placental vascularization with a view to improve the understanding of this complex vascularization.…”
Section: Introductionmentioning
confidence: 99%
“…The use of HDFI and radiant flow aids the prenatal diagnosis of an aberrant course of ductus venosus [37]. Leung KY recently described a new approach of using STIC with rendered volume in glass-body mode and TUI to facilitate the assessment of this complex venous system [38] (Figure 9). The connection of the hepatic veins, ductus venosus, and inferior vena cava to the fetal heart and their spatial relationships can be displayed in glass-body mode.…”
Section: Fetal Abdomen and Other Fetal Vesselsmentioning
confidence: 99%
“…The connection of the hepatic veins, ductus venosus, and inferior vena cava to the fetal heart and their spatial relationships can be displayed in glass-body mode. STIC cine-loop can show blood flow of the precordial venous system in a cardiac cycle with two different pathways to the right atrium [38]. Further studies are required to assess if this approach can improve the prenatal diagnosis of venous abnormalities.…”
Section: Fetal Abdomen and Other Fetal Vesselsmentioning
confidence: 99%
See 1 more Smart Citation